2017
DOI: 10.1038/oncsis.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

FAM83A is amplified and promotes cancer stem cell-like traits and chemoresistance in pancreatic cancer

Abstract: Cancer stem cells (CSCs), also known as tumor-initiating cells (TICs), contribute to tumorigenesis, resistance to chemoradiotherapy and recurrence in human cancers, suggesting targeting CSCs may represent a potential therapeutic strategy. In the current study, we found family with sequence similarity 83, member A (FAM83A) is significantly overexpressed and associated with poorer overall survival and disease-free survival in pancreatic cancer. Overexpression of FAM83A markedly promoted, whereas inhibition of FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 45 publications
(50 reference statements)
1
68
0
Order By: Relevance
“…Concordantly, researches proved that FAM83A presented high expression in several other human cancers, such as in breast, testis, bladder and pancreatic cancer [12,21,22]. Moreover, high expression level of FAM83A in pancreatic cancer was correlated with poorer survival [12]. When exploring the mechanism of FAM83A up-regulation, its genomic locus is of interest.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Concordantly, researches proved that FAM83A presented high expression in several other human cancers, such as in breast, testis, bladder and pancreatic cancer [12,21,22]. Moreover, high expression level of FAM83A in pancreatic cancer was correlated with poorer survival [12]. When exploring the mechanism of FAM83A up-regulation, its genomic locus is of interest.…”
Section: Discussionmentioning
confidence: 92%
“…Recently it was found that the DUF1669 domain of FAM83 family proteins anchored casein kinase 1 isoforms which were implicated in the regulation of many cellular processes [11]. FAM83A (originally named BJ-TSA-9) is highly expressed across tumor types [7,12,13]. In pancreatic cancer, FAM83A is amplified and promotes cancer stem cell-like traits [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAM83A is involved in regulating a variety of different tumor-related signaling pathways, including the EGFR, RAS/RAF/MEK/ERK, and PI3K/AKT/mTOR pathways (3,4). The overexpression of FAM83A has been shown in lung, breast, testicular, and bladder cancers and is associated with promoting the development of cancers (7)(8)(9)(19)(20)(21)(22). Li et al (3) reported that FAM83A is highly expressed in lung cancer tissues, especially LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance is identified as a major obstacle in tumor chemotherapy, and miRNAs have been reported to serve critical roles in this process (17)(18)(19)(20)(21)(22)(23). To date, several studies have identified that miR-149 exerts a critical function in numerous types of tumors.…”
Section: Discussionmentioning
confidence: 99%